JALUR DISTRIBUSI DAN UPAYA PERBAIKAN PASCAPANEN BUNGA POTONG KRISAN (Dendrathema grandiflora) DARI PETANI DESA PANCASARI BULELENG SAMPAI PENGECER - Lumbantoruan, Yohana Putri; Harsojuwono, Bambang Admadi; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): Desember, 2018)
The purpose of this study was 1) to determine the number of chrysanthemum distribution lines and distribution types from farmers in Pancasari to retailers, 2) to find out the system, people, and the impact of chrysanthemum postharvest handling in distribution from farmers in Pancasari to retailers, 3) to determine the impact of improvements postharvest on chrysanthemum damage from farmers in Pancasari to retailers with soaking treatment using sodium metabisulfite solution. The method used is the snowball sampling method in the form of surveys and interviews with the Commodity System Assessment Method (CSAM) application using a questionnaire. Treatment of postharvest repair by soaking the flower stalk in sodium metabisulfite solution. There are two lines in the distribution, lane I (Farmers ? Wholesalers ? Retailer ? Consumer) and lane II (Farmers ? Retailer ? Consumer). Postharvest handling includes harvesting, sorting, binding, wrapping, soaking, storing, packaging, distributing, and displaying. Impact of handling postharvest loss in the sorting stage at the farm level 2% (insignificant), wholesaler level 3% (insignificant), and retailer level 8% (significant) Post-harvest improvement can prolong the duration of freshness of flowers.Using water, chrysanthemum cut flowers can last 2.38 days, using sodium metabisulfite can last 6.25 days. Keywords : Chrysanthemum, sodium metabisulfite, CSAM, postharvest improvements.